Associated ileocaecal location is a marker for greater severity of low rectal endometriosis. (4th September 2019) - Marcellin, L; Leconte, M; Gaujoux, S; Santulli, P; Borghese, B; Chapron, C; Dousset, B
Abstract : Objective: To determine whether ileocaecal endometriosis (ICE) is a marker for low rectal endometriosis (LRE) severity. Design: Retrospective cohort study. Setting: France. Population and sample: Analysis of 375 colorectal resections performed in women undergoing complete surgery for LRE from January 1995 to December 2015 in a university centre for endometriosis. Methods: Univariate and multivariate analysis of anatomical, postoperative clinical, and long‐term outcomes according to presence of ICE. Main outcomes and measures: Mean number and type of deep infiltrating endometriosis (DIE) lesions, the existence of an associated endometrioma, and mean total American Society for Reproductive Medicine (ASRM) score. Results: The prevalence of ICE was 25.6%. Primary end‐point data showed that women with ICE had a significantly higher adjusted number of DIE lesions (OR = 1.43, 95% CI 1.02–3.03; P = 0.048), higher prevalence of endometriomas (OR = 1.91, 95% CI 1.04–3.51; P = 0.044), more associated DIE sigmoid lesions (OR = 2.12, 95% CI 1.07–3.91; P = 0.025), and a higher mean total ASRM score (OR = 2.07, 95% CI 1.12–4.14; P = 0.025). Women with ICE resected during the surgical procedure for LRE did not have more adverse postoperative clinical outcomes than ICE‐negative patients. Conclusion: Ileocaecal endometriosis was significantly associated with greater LRE severity. In a complete surgical resection strategy, combining resection of ICE and LRE did not appear to increase postoperative rates of complications, morbidity or recurrence, nor did it seem to impair long‐term clinical outcomes. Tweetable abstract: In women with low rectal endometriosis, 25% have an associated ileocaecal location that is a marker for severity. Tweetable abstract: In women with low rectal endometriosis, 25% have an associated ileocaecal location that is a marker for severity.